2021
DOI: 10.1002/hyp.14396
|View full text |Cite
|
Sign up to set email alerts
|

Streamflow regime of a lake‐stream system based on long‐term data from a high‐density hydrometric network

Abstract: Northern landscapes are dominated by a mosaic of lakes and streams, yet only a limited number of studies have explored how these lake-stream networks influence streamflow regimes. In order to gain further insight into the hydrologic behaviour of lake-stream systems, we conducted a study using long-term streamflow data to investigate the annual-, seasonal-and event-scale streamflow regimes of a lakestream network at the Turkey Lakes Watershed (TLW) in central Ontario, Canada.Streamflow metrics were compared for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 79 publications
1
12
0
Order By: Relevance
“…During short rainfall events, lakes control streamflow response by storing much of the rainfall input, resulting in lower runoff volumes during rainfall events. The results are similar to those obtained by Hudson et al (2021), who found that catchments that have larger lake percentages can reduce the peak flow magnitude and delay peak flow occurrence, especially during short rainfall events. Arp et al (2006) also investigated how stream‐lake landscapes contribute to flood reduction by analysing the timing and magnitude of peak flow during snowmelt and storm events.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…During short rainfall events, lakes control streamflow response by storing much of the rainfall input, resulting in lower runoff volumes during rainfall events. The results are similar to those obtained by Hudson et al (2021), who found that catchments that have larger lake percentages can reduce the peak flow magnitude and delay peak flow occurrence, especially during short rainfall events. Arp et al (2006) also investigated how stream‐lake landscapes contribute to flood reduction by analysing the timing and magnitude of peak flow during snowmelt and storm events.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, we used observed streamflow recorded at the C7 station 5 h before the start of each rainfall event as another indicator of antecedent storage (referred to as antecedent reference discharge) (Hudson et al, 2021; Wilson et al, 2011). We used specific discharge at C7 sub‐catchment, following Tiwari et al (2022), as it is located in the central part of Krycklan, drains a mix of mire and forest land covers, and has a mean specific discharge comparable to that of all other sub‐catchments; therefore, the use of C7 allows for a consistent and standardized measurement across all sites.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, a plurality of training sets are formed through the Porter sampling method, and a fault early warning decision tree is constructed on the generated training sets by using the decision tree algorithm. In this process, the kmodes clustering algorithm is used to generate early warning strategies [10].…”
Section: Establish a Fault Early Warning Modelmentioning
confidence: 99%
“…In contrast, lake influences on downstream discharge are more variable. Other studies have highlighted the moderating influence of lakes on stream flow (Dorava & Milner, 2000;Epstein et al, 2013;FitzGibbon & Dunne, 1981;Hudson et al, 2021;Jones et al, 2014); however, this influence may be negligible when a lake's capacity to attenuate streamflow is exceeded, such as during spring freshet (Arp et al, 2006;Goodman et al, 2011;Karlsen et al, 2016) or as one moves further downstream from the lake . In more arid regions, the storage deficit in lakes during summer is often sufficiently high that precipitation events do not cause water levels to exceed storage capacity, resulting in intermittent downstream flows (Baki et al, 2012;Kusumastuti et al, 2008;Spence et al, 2010;Woo and Woo & Mielko, 2007).…”
Section: F I G U R Ementioning
confidence: 99%